La cultura popular: problemática y líneas de investigación - Gilberto Giménez (Estudios sobre las Culturas Contemporáneas)
Before the exposure of a research proposal for the understanding and analysis of popular cultures, tKe author makes a critical examination of the patadigm from which he starts. He begins reviewing the meaning of the syntagma "popular culture", the establishes a conceptual system, of Gramsciaii inspiration and developed by Alberto Cirese, as the analytical framework for his proposal, which outlines two cultural areas: the first one^ corresponds to the festival or ceremonial cidture, and the second one, to daily life. Here the social imaginary must be analyzed in order to catch its real meaning.